Prevalence of major depressive disorders and suicide in long-term care facilities: A report from northern Thailand - Nahathai Wongpakaran (2018)
Background: Depression is a common mental illness among elderly Thais, but little is known about the occurrence of major depressive disorders (MDD) in long-term care (LTC) facilities. This study investigated the prevalence of MDD and suicide risk among residents in an LTC facility in northern Thailand. Methods: For this cross-sectional study, a care team conducted a screening program for MDD and suicide risk among LTC residents in 2011. The screening process used the Mini International Neuropsychiatric Interview, the Geriatric Depression Scale-15, the patient and caregiver versions of the Cornell Scale for Depression in Dementia, the Core Symptom Index and the Mini Mental State Examination. Results: In total, 81 (of 113) residents participated in the study. The mean age was 76.96 ± 7.17years old (range, 63-94), and 55.6% of participants were women. With the Mini Mental State Examination, 40.7% were found to have cognitive impairment, and with the Mini International Neuropsychiatric Interview, 23.5% met the criteria for current major depressive episodes. Though the majority was in the low-risk group, 26 residents (32.1%) were reported as being at risk of suicide. The patient and caregiver versions of the Cornell Scale for Depression in Dementia, the Geriatric Depression Scale-15 and the Core Symptom Index proved useful for predicting major depressive episodes among the residents (P < 0.001, P= 0.004, P= 0.001 and P < 0.001, respectively), including those with cognitive impairment (P= 0.006, P= 0.020, P= 0.049 and P= 0.012, respectively). Conclusions: Nearly one-quarter of LTC facility residents were found to suffer from MDD, and a suicide risk was reported for one-third, though most of the cases were in the low-risk category. Further studies with a larger sample size are recommended to make these findings more precise and universally applicable. © 2012 The Authors. Psychogeriatrics © 2012 Japanese Psychogeriatric Society.